A new variety of Pyrus hyrcana Fed. (Rosaceae) from Vayots Dzor province of Armenia - Akopian, J. A. (Армянское ботаническое общество)
A new variety Pyrus hyrcana Fed. var. yeghegisi Akopian found in the gorge of the Yeghegis River, in the vicinity of the village Vardahovit of Vayots Dzor province of Armenia has been described. Morphological description of the new variety based on the studies in flowering, fruiting and early stages of development has been carried out. Distinctive features of P. hyrcana var. yeghegisi and P. hyrcana var. hyrcana are presented. The article is illustrated with original photographs. Նկարագրված է Pyrus hyrcana Fed. var. yeghegisi Akopian տանձենու նոր տարատեսակ, որը հայտնաբերվել է Եղեգիս գետի կիրճում, Հայաստանի Վայոց ձորի մարզի Վարդահովիտ գյուղի շրջակայքում: Կատարվել է նոր տարատեսակի մորֆոլոգիական նկարագրությունը` ծաղկման, պտղաբերման և զարգացման վաղ փուլերի ուսումնասիրության հիման վրա: Բերվում են P. hyrcana var. yeghegisi- ի և P. hyrcana var. hyrcana-ի տարբերակիչ հատկանիշները: Հոդվածը պատկերված է օրիգինալ լուսանկարներով: Описанa новая разновидность Pyrus hyrcana Fed. var. yeghegisi Akopian, найденная в ущелье реки Ехегис, в окрестностях селeния Вардаовит области Вайоц Дзор Армении. Выполнено морфологическое описание новой разновидности, основаннoе на изучении цветeния, плодоношения и ранних стадий развития. Приводятся отличительные признаки P. hyrcana var. yeghegisi от P. hyrcana var. hyrcana. Статья иллюстрирована оригинальными фотографиями.
Keywords: Botany